Peran Teknologi Digital dalam Meningkatkan Daya Saing UMKM di Era Digitalisasi - Budi Sihotang (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This study aims to analyze the role of digital technology in improving the competitiveness of MSMEs in the digitalization era. Digital technologies, such as social media, e-commerce platforms, digital payment systems, and management software, have brought significant changes in the operations and marketing strategies of MSMEs. The results show that the adoption of digital technologies can improve productivity, product differentiation, and customer communication, leading to an average 35% increase in turnover and higher operational efficiency. Nevertheless, challenges such as limited digital literacy, high adoption costs, and uneven internet infrastructure are still obstacles for most MSMEs. Therefore, it is recommended that MSMEs improve digital literacy through training and selection of more affordable technology solutions, while the government and technology providers need to expand stable internet access and provide subsidies for technology devices. This study also identified some limitations, such as limited location coverage, and suggests future research to expand the research area and use a more in-depth quantitative approach to gain a more comprehensive understanding of the impact of digital technology on MSMEs.